How well are women being debriefed on perineal care following episiotomies and vaginal tears after childbirth?. (18th April 2012) - Kindinger, L; Touqmatchi, D; Phelan, L
Abstract : Introduction: Episiotomies are the most commonly performed surgical procedure. Approximately 85% of women will sustain a vaginal tear at delivery, with 70% requiring suturing. NICE guidelines advise on care and management of perineal tears. Given the importance of this, we assessed how women were debriefed within our department on the care of their perineal wound. Methods: Questionnaires on perineal trauma were distributed to patients on the postnatal ward. Data collected included awareness of their type of tear, who sutured it, advice regarding analgesia, signs of infection, wound hygiene, bladder and bowel care, pelvic floor exercises and resuming sexual intercourse. Results: 61 responses were collated. 41% were sutured by a midwife and 59% by an obstetrician. 70% were unaware of their degree of tear. Less than 50% were advised on symptoms of infection or wound breakdown. Discussion on oral analgesia, pad changes and washing were reported as 72%, 74% and 87% respectively. Only 21% were counseled on resumption of sexual intercourse. Debrief on pelvic floor exercises, urinary and bowel functions were reported at 65%, 64% and 52%. Patients reported the postnatal ward midwives as the most informative (57%), with only 44% of advice coming from the person suturing. 93% stated they would benefit from written advice. Conclusions: Women with perineal trauma are not fully informed. It is the duty of the person suturing to debrief women on perineal tears. In addition to highlighting the importance of this to staff during suturing, information leaflets have been devised for patients to take home.